2020
DOI: 10.15448/1677-9509.2020.1.36997
|View full text |Cite
|
Sign up to set email alerts
|

Políticas sociais direcionadas às famílias com chefia feminina

Abstract: O artigo apresenta parte dos resultados de uma investigação relativa ao projeto de cooperação internacional, envolvendo Brasil e Portugal, referente às diferenças e similitudes entre as políticas familiares de conciliação entre trabalho profissional e o trabalho familiar direcionadas as famílias com chefia feminina. A partir de levantamento bibliográfico, a revisão sistemática da literatura na área, identificam-se pontos de aproximação e distanciamento entre os autores estudados, como: à discussão da implantaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The evaluation of the family group, a clinical task of situation analysis, allows the primary care professional to understand the ways in which the different health conditions arise, such as why alcoholism has a high family incidence or why a patient with hypertension has difficulty controlling their hypertension. Minuchin [9] describes the situation of identical twin sisters with diabetes mellitus who had unequal control of their disease; when analyzing the family relations of these girls, it is found that the one who had a bad control of the disease was the one that triangulated with the parents in their problems of relationship-whenever they fought she made a crisis in their diabetes. It is common to comment in classes on hypertension that if the patients follow the professional's guidelines, they would not have consequences of their disease, but unfortunately the hypertensive patient is very difficult to deal with.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of the family group, a clinical task of situation analysis, allows the primary care professional to understand the ways in which the different health conditions arise, such as why alcoholism has a high family incidence or why a patient with hypertension has difficulty controlling their hypertension. Minuchin [9] describes the situation of identical twin sisters with diabetes mellitus who had unequal control of their disease; when analyzing the family relations of these girls, it is found that the one who had a bad control of the disease was the one that triangulated with the parents in their problems of relationship-whenever they fought she made a crisis in their diabetes. It is common to comment in classes on hypertension that if the patients follow the professional's guidelines, they would not have consequences of their disease, but unfortunately the hypertensive patient is very difficult to deal with.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of inclusion is so impotent that it is a cornerstone in the systemic structural therapy proposed by Minuchin [9]. And how does inclusion work?…”
Section: Inclusionmentioning
confidence: 99%